Italian participation to the WHO action network on measuring health literacy: policy implications. (13th November 2019) - Cadeddu, C; Palmieri, L; Galeone, D; Mastrilli, V; D'Elia, R; Rosano, A
Abstract: Issue: Health literacy (HL) is recognized as a determinant, mediator or moderator of health and of use and results of health care services Inadequate HL is associated with patient disengagement, inappropriateness of care, increased health care costs, and higher mortality rates. Description of the problem: Few previous studies suggested that inadequate HL is a prevailing problem in Italy. As compared with the European Countries, Italy has peculiar characteristics of socio-demographic determinants of HL levels, which constitute a challenge for policy making. In so far HL has not been considered as a strategic priority for the Italian National Health Service. The Italian National Institute of Health and Ministry of Health are promoting a national program on HL by adhering to the WHO action network on measuring population and organizational health literacy (M-POHL). Main aim of the program is to propose policies that could enable all citizens to share the benefits of improved HL. A national population survey, coordinated at European level, has been planned in each participating country in 2019. Preliminary results: We are setting up the survey using the questionnaire with 47 specific questions about HL and 32 about lifestyles and demographic characteristics. Updated results of this survey will be analysed in order to define a strategic line for the implementation of actions for the improvement of HL in the next National Prevention Plan. Furthermore, the national survey will be scheduled and repeated to monitor results. Lesson State: Policies can be implemented at individual, community, organization or system level. Italy is at the beginning of its experience in this field. A national steering committee of experts has also been appointed to support HL policy initiatives. The comparison with existing policies in other countries within the M-POHL action will be another asset to develop HL policies and related activities to benefit citizens, patients and communities.